2021
DOI: 10.1108/lodj-02-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Executive coaching: an exploration of the coachee's perceived value

Abstract: PurposeThe goal of this qualitative study is to explore how different elements of the coach–coachee setting can affect the perceived outcome from coaching sessions by the coachee.Design/methodology/approachUsing thematic analysis on 197 semi-structured interviews of bank executives, the authors suggest an evidence-based sequential model on how the perceived value of the coaching process might be contingent on four elements.FindingsAs a result of the exploratory analysis, the authors’ suggest that the coach's g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…This is because clients must own their goals, whereas coaches' role is to support and guide clients towards the attainment of that goal-their direct involvement in goal setting, therefore, could be detrimental to clients' success. Finally, Mosteo et al (2021) showed that coachs' guidance and coachees' self-awareness lead to coachees' perceiving coaching as valuable. In line with our results, this idea suggests that coaches should put emphasis on the capacity of their clients to initiate their reflection by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This is because clients must own their goals, whereas coaches' role is to support and guide clients towards the attainment of that goal-their direct involvement in goal setting, therefore, could be detrimental to clients' success. Finally, Mosteo et al (2021) showed that coachs' guidance and coachees' self-awareness lead to coachees' perceiving coaching as valuable. In line with our results, this idea suggests that coaches should put emphasis on the capacity of their clients to initiate their reflection by themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, there is still a great lack of scientific studies that focus on coaching and the relationship between coach and coachee, which is actually the essential condition for the success of coaching [21]. Indeed, it is known that the connection between coach and coachee has a high impact on coaching outcomes [22,23]. De Haan [19] reported, for example, the coach qualities valued by coachees, such as listening, understanding, and encouraging.…”
Section: The Relationship Between Coach and Coachee And Differences W...mentioning
confidence: 99%